Design of novel dispirooxindolopyrrolidine and dispirooxindolopyrrolothiazole derivatives as potential antitubercular agents. Issue 19 (1st October 2015) - Mhiri, Chourouk; Boudriga, Sarra; Askri, Moheddine; Knorr, Michael; Sriram, Dharmarajan; Yogeeswari, Perumal; Nana, Frédéric; Golz, Christopher; Strohmann, Carsten
Graphical abstract